2021
DOI: 10.5114/aoms.2019.86622
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of microRNA-130b improves doxorubicin sensitivity in bladder urothelial carcinoma by negatively regulating cylindromatosis expression

Abstract: Introduction: Chemotherapeutic resistance reduces the sensitivity of bladder urothelial carcinoma (BUC) to chemotherapeutic drugs and contributes a barrier leading to treatment failure. The purpose of this research project is to investigate the regulatory effects of miR-130b on chemotherapeutic drug resistance of BUC and its mechanism. Material and methods: The relative expression of miRNA-130b and cylindromatosis (CYLD) was examined using real-time quantitative PCR. The cell proliferation and doxorubicin sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The increased expression of miR-130b was negatively related to DOX sensitivity in patients with bladder carcinoma. [33] Furthermore, we observed that differences in circRNA expression were only evident at specific doses (Figure 2A,B). Both Figures 2A and 2B clearly show a significant difference between MYO-treated and control cells.…”
Section: Discussionmentioning
confidence: 85%
“…The increased expression of miR-130b was negatively related to DOX sensitivity in patients with bladder carcinoma. [33] Furthermore, we observed that differences in circRNA expression were only evident at specific doses (Figure 2A,B). Both Figures 2A and 2B clearly show a significant difference between MYO-treated and control cells.…”
Section: Discussionmentioning
confidence: 85%
“…Though this review focuses on miRNAs, there are other non-coding RNAs, such as long non-coding RNAs and circular RNAs, that have similarly been implicated in BCa resistance and recurrence and which should be explored further, especially since these networks also involved miRNAs [ 51 , 130 , 131 , 132 ]. This includes Cdr1as, a circular RNA that mediates bladder cancer chemotherapeutic response via miR-1270 [ 132 ] and circ-BPTF, which promotes recurrence through interaction with miR-31-5p [ 133 ].…”
Section: Discussionmentioning
confidence: 99%